Remoção de Cetoprofeno em Efluente por Wetlands Construídos integrados a Processos Eletroquímicos de Oxidação Avançada em pH próximo ao neutro - ISABEL MAXIMO CORRÊA DE ALCANTARA (2025)
Emerging contaminants are a broad group of compounds that include various classes of organic substances. Pharmaceuticals, in particular, are of significant concern due to their resistance to biodegradation, allowing them to persist in ecosystems and pose harmful effects on the environment and human health. Non-steroidal antiinflammatory drugs are pollutants found in wastewater, among which ketoprofen (KET) holds a prominent position due to its widespread use worldwide. The main sources of contamination are wastewater treatment plants, which generally exhibit low removal efficiency for this class of contaminants. In this context, this study aimed to evaluate the efficiency of ketoprofen removal from real effluents of a wastewater treatment plant using a combined system of vertical-flow constructed wetlands and advanced electrochemical oxidation processes (CW+AEOP). The processes of anodic oxidation (AO-H2O2), electro-Fenton (EF), and photoelectro-Fenton (PEF) were compared. The electrochemical device consisted of a platinum anode and a carbon-PTFE air-diffusion cathode. An experimental plan of the central composite design type, with triplicates at the central point, was applied to EF and PEF to investigate the effects of three independent variables: current density, Fe³⁺ concentration, and the molar ratio of the [Fe³⁺:Citrate] complex. The results demonstrated the best performance when UV irradiation and electrolysis with the Fenton reagent were simultaneously applied. Degradation efficiency was observed in the order: photoelectro-Fenton > electro-Fenton > anodic oxidation. The electrochemical processes studied demonstrated good performance in the removal of ketoprofen (> 80%), with partial mineralization (< 50%). The integrated system of vertical flow constructed wetland combined with the photoelectro-Fenton process achieved 100% degradation of ketoprofen and 90,7% mineralization. The toxicity of the studied effluents was assessed using bioindicator tests with Artemia salina and Lactuca sativa. The CW+EF and CW+FEF system showed reduction in toxicity for both bioindicators. The findings highlight that Nature-Based Solutions, combined with advanced technologies, are innovative and effective methods for wastewater treatment.